Emotional climate, feeding practices, and feeding styles: an observational analysis of the dinner meal in Head Start families - Hall Sharon K; Nicklas Theresa A; Cross Matthew B; Papaioannou Maria A; Power Thomas G; Hughes Sheryl O; Shewchuk Richard M (BMC, 2011)
Abstract Background A number of studies conducted with ethnically diverse, low-income samples have found that parents with indulgent feeding styles had children with a higher weight status. Indulgent parents are those who are responsive to their child's emotional states but have problems setting appropriate boundaries with their child. Because the processes through which styles impact child weight are poorly understood, the aim of this study was to observe differences in the emotional climate created by parents (including affect, tone of voice, and gestures) and behavioral feeding practices among those reporting different feeding styles on the Caregiver's Feeding Styles Questionnaire. A secondary aim was to examine differences on child weight status across the feeding styles. Methods Participants were 177 Head Start families from Houston, Texas (45% African-American; 55% Hispanic). Using an observational approach, the relationship between the observed emotional climate of the meal, behavioral feeding practices, and self-reported parent feeding styles were examined. Mean age of the children was 4.4 years (SD = 0.7) equally distributed across gender. Families were observed on 3 separate dinner occasions. Heights and weight were measured on the parents and children. Results Parents with self-reported indulgent feeding styles made fewer demands on their children to eat during dinner and showed lower levels of negative affect and intrusiveness. Surprisingly, these parents also showed higher levels of emotional detachment with their children during dinner. Hispanic boys with indulgent parents had significantly higher BMI z scores compared to Hispanic boys in the other three feeding style groups. No other differences were found on child weight status. Conclusions Results suggest that the emotional climate created by indulgent parents during dinner and their lack of demands on their children to eat may play an important role in how young children become overweight. Numerous observed emotional climate and behavioral differences were found between the other self-reported feeding styles as well. Results suggest that parents' self-reported feeding styles may be a proxy for the emotional climate of the dinner meal, which may in turn influence the child's eating behaviors and weight status.